تأثير الفكر الرياضي في أعمال عبد الرحمن الحاج صالح - بومحديو, نسيمة (جامعة الوادي - University of Eloued, 2019)
هدفنا من هذه الدّراسة إبراز تأثر الدّكتور عبد الرحمن الحاج صالح بالفكر الرياضي وكيف استغلّه لخدمة اللغة العربية خصوصا فيما بعرف بالمدرسة الخليلية الحديثة. ثمّ هل لهذا الجهد المبذول علاقة بحوسبة اللغة العربية أو ما يعرف بمشروع "الذخيرة اللغوية". سنقسّم الدّراسة إلى قسمين: الأوّل: الظواهر اللغوية التي فسّرها عبد الرحمن الحاج صالح تفسيرا رياضيا. الثاني: مشروعا المدرسة الخليلية و الذخيرة اللغوية و استعانتهما بالفكر الرياضي. The objective of this study is to highlight how Dr. Abderrahmane Hadj Salah got influenced by mathematical thinking and he made use of this knowledge to serve the Arabic language namely in what is known as the Modern Khalili’s school. The question we want to answer is whether the effort deployed has a relation with the computerization of Arabic or with the project known as " the Arabic corpus" . The study is divided into two parts : The first part deals with the linguistic aspects which Abderrahmane Hadj Salah explained mathematically. The second part deals with the project of the Khalili’s school and of the Arabic corpus and the use they made of mathematics.
مقال
Keywords: تأثر ; رياضيات ; ذخيرة لغوية ; مدرسة خليلية ; عبد الرحمن الحاج صالح